2D/3D Copper-Based Metal-Organic Frameworks for Electrochemical Detection of Hydrogen Peroxide - Guo, Xiangjian; Lin, Chuyan; Zhang, Minjun; Duan, Xuewei; Dong, Xiangru; Sun, Duanping; Pan, Jianbin; You, Tianhui (Frontiers in Chemistry, 2021)
ABSTRACT: Metal-organic frameworks (MOFs) have been extensively used as modified materials of electrochemical sensors in food industry and agricultural system. In this work, a comparison of two kinds of copper-based MOFs (Cu-MOFs) with two dimensional (2D) sheet-like structure and three dimensional (3D) octahedral structure for H2O2 detection was studied. The synthesized 2D and 3D Cu-MOF were modified on the glassy carbon electrode to fabricate electrochemical sensors, respectively. The sensor with 3D Cu-MOF modification (HKUST-1/GCE) presented better electrocatalytic performance than the 2D Cu-MOF modified sensor in H2O2 reduction. Under the optimal conditions, the prepared sensor displayed two wide linear ranges of 2 μM to 3 mM and 3 mM to 25 mM and a low detection limit of 0.68 μM. In addition, the 3D Cu-MOF sensor exhibited good selectivity and stability. Furthermore, the prepared HKUST-1/GCE was used for the detection of H2O2 in milk samples with a high recovery rate, indicating great potential and applicability for the detection of substances in food samples. This work provides a convenient, practical, and low-cost route for analysis and extends the application range of MOFs in the food industry, agricultural and environmental system even in the medical field with more possibility.